Rangelands and Their Improvement in India - Singh, Panjab (Annals of Arid Zone, 2016)
Grasslands are the major feed resources for livestock rearing in India since time immemorial. Due to extremities of climate, poor management and the constraints of grazing, these areas have been degraded at an alarming rate. Due to high grazing pressure and low to very low carrying’ capacity these grasslands have undergone tremendous changes and now pose a serious threat and challenge for rehabilitation and ecorestoration of their depleted resources. It calls for an integrated approach for management of the vast grassland areas. Technological opportunities available for restoration, regeneration and enhancement of biomass production require large scale development efforts. Future thrust areas of R&D lay emphasis, besides others, on utilization of grasslands, protection of grasslands, stocking rates, ecosystem rehabilitation and people’s participation in the entire gamut of activities. Stress is to be given on production, management and utilization for sustainable development.